PENGARUH PERAN KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA (Studi Pada Yayasan Pembinaan dan Pendidikan Islam Al- Hidayah) - Meilani, Seila (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2024)
This study seeks to examine the impact of leadership roles, the work environment, and work motivation on job satisfaction within the Al-Hidayah Islamic Education and Training Foundation. The participants in this study were educators affiliated with the Al-Hidayah Islamic Education and Training Foundation. The study involved a population and sample of 70 teachers, utilizing a sampling technique referred to as saturated sampling. The analytical approach employed was the Partial Least Squares (PLS) technique, which was executed using the SmartPLS statistical software, with a questionnaire serving as the research instrument. The findings of the research suggest that leadership positions do not influence job satisfaction levels among educators at the Al- Hidayah Islamic Education and Training Foundation. In a similar vein, the work environment appears to exert no influence on job satisfaction, and work motivation does not impact job satisfaction among the teachers at the foundation as well.